2020
DOI: 10.3390/molecules25071514
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Isotopically Labelled Standards of Creatinine Via H/D Exchange and Their Application in Quantitative Analysis by LC-MS

Abstract: Kidneys play a crucial role in maintaining metabolic homeostasis in a body. Serum creatinine concentration is a simple test used as an indicator of renal function. One of the known ways of quantifying creatinine concentration is the liquid chromatography-mass spectrometry (LC-MS) method, using an isotopically labeled analog of creatinine as an internal standard. Unfortunately, such isotope-labeled analogs are expensive and their synthesis is complex. Here we demonstrate a facile preparation of deuterated analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recently, Bąchor et al [ 69 ] used the liquid chromatography–mass spectrometry (LC-MS) method with an isotopically labelled analogue of creatinine as an internal standard for quantifying the creatinine concentration in urine. This method of preparation of deuterated analogues of creatinine, via the H/D exchange of hydrogens located at the α-carbon (α-C) of the N -methylated amino acid part, under basic conditions may be successfully used for the creatinine concentration in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bąchor et al [ 69 ] used the liquid chromatography–mass spectrometry (LC-MS) method with an isotopically labelled analogue of creatinine as an internal standard for quantifying the creatinine concentration in urine. This method of preparation of deuterated analogues of creatinine, via the H/D exchange of hydrogens located at the α-carbon (α-C) of the N -methylated amino acid part, under basic conditions may be successfully used for the creatinine concentration in saliva.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently we developed a method of deuterium-labeled standard preparation of creatinine, a breakdown product of creatine phosphate in muscle and a molecular biomarker of renal function [ 48 ]. The N -methylated glycine moiety was also presented within the creatinine molecule.…”
Section: Hydrogen−deuterium Exchange At Carbon Centersmentioning
confidence: 99%
“…Recently, we reported our investigation on the hydrogen–deuterium exchange of carbon-bounded hydrogen atoms in peptides containing N -substituted glycine and alanine residues, via base-catalyzed hydrogen–deuterium exchange [ 22 , 23 , 24 , 25 ]. This observation allowed us to developed methods of deuterated standards preparation of denatonium benzoate [ 26 ], cyclosporine A [ 27 ] and creatinine [ 28 ], which were successfully applied in their quantification by LC-MS. We found that the introduced deuterons do not undergo back-exchange either in an acidic or neutral conditions and that the isotopologues co-elute.…”
Section: Introductionmentioning
confidence: 99%